EVALUASI KEPUASAN PENGGUNA SISTEM E-PERSEDIAAN KABUPATEN BONE BOLANGO MENGGUNAKAN MODEL EUCS DAN DELONE AND MCLEAN - Malapu, Nayla Yuniar; Amali, Lanto Ningrayati; Zakaria, Alfian (Gorontalo State University, 2025)
Bone Bolango Regency has implemented the E-Inventory Information System in the financial sector. However, issues persist, such as data not appearing during reviews and duplicate entries despite single inputs, affecting information accuracy. This study aims to identify factors influencing user satisfaction, determine the most influential variables, and provide improvement recommendations. The models employed are End User Computing Satisfaction (EUCS) and DeLone McLean, with analysis conducted using PLS-SEM. The research findings indicate t-test values for content (0.974), accuracy (1.620), format (1.215), ease of use (0.089), timeliness (2.368), information quality (0.860), system quality (1.115), and service quality (1.142). Among all dimensions, only timeliness significantly impacts user satisfaction. Keywords : End User Computing Satisfaction (EUCS); Delone and McLean; User Satisfaction; PLS-SEM